(untitled) (Journal of Plant Disease Sciences, 2021)
Development of resistant varieties is the viable strategy to overcome wilt of chickpea caused by Fusarium oxysporum f.sp. ciceri (Padwick) Synd. & Hans. However, difficulties associated with the development and maintenance of uniform wilt sick plots for screening have hindered the process of developing resistant cultivars. Thus, there is a need for more efficient methods for screening cultivars against the disease. In this regards these resistant sources by screening promising entries will be identified for F. oxysporum f. sp. ciceri race specific isolates and new variant. Studies on host resistance under multiple disease sick field led to conclusion that among 285 entries two entries showed less than 10 percent mortality and may be considered as resistant, 11 entries exhibited 10.1 to 20 percent mortality and regarded as moderately resistant during first year, however in secon year six entries showed less than 10 percent mortality and considered as resistant, 14 entries exhibited 10.1 to 20 percent mortality and regarded as moderately resistant.